Is the introduction of violence and injury observatories associated with a reduction in violence-related injury in adult populations? A systematic review and meta-analysis. Issue 7 (31st July 2019) - Jabar, Ardil; Fong, Francisco; Chavira, Monica; Cerqueira, Maria Teresa; Barth, Dylan; Matzopoulos, Richard; Engel, Mark E
Abstract : Objective: The aim of this study was to summarise the results from existing studies reporting on the effectiveness of the introduction of violence and injury observatories (VIOs). Design: This is a systematic review and meta-analysis study. Data sources: We searched multiple electronic databases including but not limited to PubMed, PsycINFO, SCOPUS, Cochrane Collaboration, Campbell Collaboration and Web of Knowledge. Eligibility criteria: We included non-randomised controlled trials, quasi-experimental designs, prospective and retrospective cohort studies, controlled before-and-after studies and cross-sectional studies. We sought to include studies performed in any country and published in any language. The primary outcome was homicide, while the secondary outcome was assault. Data extraction and synthesis: We searched a number of databases, supplemented by searches in grey literature including technical reports. Searches comprised studies from January 1990 to October 2018. Results: Of 3105 potentially relevant unique citations from all literature searches, 3 empirical studies and 4 technical reports met our inclusion criteria. Studies were conducted in the UK (n=3), Colombia (n=2), Brazil (n=1) and Uruguay (n=1). Subgroup analyses according to the two types of models implemented, the VIO and the injury surveillance system (ISS), provided evidence for an association between implementing the VIO model and a reduction in homicide count in high-violence settings (incidence rate ratio (IRR)=0.06; 95% CI 0.02 to 0.19; four studies), while the introduction of ISS showed significant results in reducing assault (IRR=0.80; 95% CI 0.71 to 0.91; three studies). Conclusion: This systematic review provides the best evidence available for the effectiveness of the introduction of VIOs and ISSs in reducing violence outcomes in adults in high-violence settings. The implementation of VIOs should be considered in high-violence communities where reduction in homicide rates is desired. PROSPERO registration number: CRD42014009818.